WHEN FEAR NARROWS THE MIND: THE INDIRECT IMPACT OF EMOTIONAL STUMBLING BLOCKS ON EFFECTIVE PROBLEM-SOLVING - Mpumelelo Longweni (PEOPLE: International Journal of Social Sciences, 2026)
If the influence of the emotional stumbling block (EB) on managers’ thinking skills is not understood, it may leave their creative problem-solving (CPS) process aimless. There is a need for empirical research to bridge this gap. The primary aim of this study is to explore the impact of thinking skills and the emotional stumbling block on managers’ effective problem-solving competency (EPS). This article addresses this apparent contextual gap with a quantitative study from a managerial science perspective within the agricultural industry. The empirical component of this explorative investigation was carried out through a survey and using a quantitative research approach. The sample included middle and lower managers from five major agricultural cooperative businesses. A total of 338 usable questionnaires were analysed. The data was analysed using jamovi to run a series of regressions estimating the relationships among independent variables, mediator and the dependent variable. The Preacher and Hayes bootstrapping method was employed with 10 000 bootstrapped samples. This study found that effective problem-solving is innately linked to divergent thinking (DT) and convergent thinking (CT). Divergent thinking directly leads to effective problem-solving, meaning that deferring judgement to be expansive during idea generation is needed for effective problem-solving. Convergent thinking fully mediates this relationship by narrowing the multitude of possible ideas to find the most effective and efficient solutions. To the best of the author’s knowledge, this article is the first to empirically prove this mediation path in this manner. Effective problem-solving is highly stifled by the emotional stumbling block through convergent thinking. Emotions such as fear of failure and insecurity only hamper managers’ problem-solving competency via their divergent thinking to a negligible extent. Unless the nuanced impact of this hindrance is understood and dealt with, managers’ creative potential through their effective thinking skills may become futile.